INTERVENSI UNTUK MENINGKATKAN EFIKASI DIRI MENYUSUI : LITERATUR REVIEW - Hanifatur Rosyidah; Noveri Aisyaroh; Ratih Fajar Wati (JURNAL MEDIA KESEHATAN, 2022)
Background: Self efficacy is belief in one's ability to achieve goals or perform tasks and can affect personal motivation and ability to succeed in breastfeeding. The self efficacy beliefs of postpartum women facilitate or hinder the condition of facing difficulties that arise with breastfeeding practices on the 120th and 180th postnatal days. The Short Form Breastfeeding Efficacy Scale (BSES-SF) was used to assess the self efficacy of early breastfeeding in postpartum women. Methods: The author uses the Systematic Literature Review (SLR) method from the PubMed database reference with the keywords Breastfeeding Self Eficacy (BSE) from 2014 - 2021. Result: From 14 articles taken as reference sources, there are 10 interventions that can be applied to increase the level of self efficacy in breastfeeding mothers. Conclusion: Based on the results of the literature review, there were 9 interventions that matched the inclusion criteria which were known to be used as an effort to reduce depression symptoms in postpartum mothers, namely skin to skin contact, web based monitoring, counseling, interpersonal counseling about exclusive breastfeeding, breastfeeding motivation programs, telephone, flipchart, computer based breastfeeding education, smartphone based breastfeeding education, Kangoroo mother care. Keywords: Exclusive breastfeeding, Breastfeeding Self Efficacy, Self efficacy, Short Form Breastfeeding Efficacy Scale.